AIAA Atmospheric Flight Mechanics Conference and Exhibit 2005
DOI: 10.2514/6.2005-6027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unsteady Aerodynamic Modelling Methodologies with Respect to Flight Loads Analysis

Abstract: This paper addresses the development of aircraft models for flight loads analysis in the pre-design stage. The underlying model structure consists of the nonlinear equations of motion of a free flying, flexible aircraft, as well as a model, which calculates the distributed aerodynamics over the entire airframe.Different possibilities in modelling the unsteady aerodynamic interactions for pre-design purposes are explored and the effects on the loads are compared in order to assess the tradeoffs between accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 4 publications
1
34
0
Order By: Relevance
“…Suitable model reduction approaches [3][4][5][6][7] are hence increasingly in demand, among which fast semi-analytical calculations of the aerodynamic loads due to both aircraft motion and wind gusts are still highly desirable [8][9][10] for efficient aeroelastic stability analysis and structural sizing, especially in the context of wing multidisciplinary design and optimisation (MDO) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Suitable model reduction approaches [3][4][5][6][7] are hence increasingly in demand, among which fast semi-analytical calculations of the aerodynamic loads due to both aircraft motion and wind gusts are still highly desirable [8][9][10] for efficient aeroelastic stability analysis and structural sizing, especially in the context of wing multidisciplinary design and optimisation (MDO) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ricciardi loads computation was shown using a dynamic simulation of a transport aircraft. Kier [22] applied different aerodynamic theories to Reschke's work and compared the computational cost and resulting loads. The gust response was calculated for a range of symmetric 1-cosine gust inputs.…”
Section: Coupled Flight Dynamics and Aeroelasticitymentioning
confidence: 99%
“…Such coupling is, in general, not supported by commercial aeroelastic finite element codes, such as Nastran, which consider only linear flight mechanics for loads and stability analyses. Significant efforts has been made trying generate aircraft models combining flight dynamics and airframe structural flexibility [3][4][5][6][7][8][9][10][11][12][13] however this is still not a common practice for industrial applications which has found MBS to be a more straight forward approach.…”
mentioning
confidence: 99%